Gender and Family Disparities in Suicide Attempt and Role of Socioeconomic, School, and Health-Related Difficulties in Early Adolescence - Chau, Kénora (Hindawi Publishing Corporation, 2014)
Suicide attempt (SA) is common in early adolescence and the risk may differ between boys and girls in nonintact families partly because of socioeconomic, school, and health-related difficulties. This study explored the gender and family disparities and the role of these covariates. Questionnaires were completed by 1,559 middle-school adolescents from north-eastern France including sex, age, socioeconomic factors (family structure, nationality, parents' education, father's occupation, family income, and social support), grade repetition, depressive symptoms, sustained violence, sexual abuse, unhealthy behaviors (tobacco/alcohol/cannabis/hard drug use), SA, and their first occurrence over adolescent's life course. Data were analyzed using Cox regression models. SA affected 12.5% of girls and 7.2% of boys (P < 0.001). The girls living with parents divorced/separated, in reconstructed families, and with single parents had a 3-fold higher SA risk than those living in intact families. Over 63% of the risk was explained by socioeconomic, school, and health-related difficulties. No family disparities were observed among boys. Girls had a 1.74-time higher SA risk than boys, and 45% of the risk was explained by socioeconomic, school, and mental difficulties and violence. SA prevention should be performed in early adolescence and consider gender and family differences and the role of socioeconomic, school, and health-related difficulties.